Managing academic libraries principles and practice - Higgins, Susan E. (Cambridge, MA Chandos Publishing, 2017)
Managing Academic Libraries: Principles and Practice is aimed at professionals within the Library and Information Services (LIS) who are interested in learning more about the management of academic libraries. Written against a backdrop made up of the changes that digital technology has brought to academic libraries, this book uncovers how the library has changed its meaning from a physical to virtual icon and its effect on culture.
The book aims to provide managers and students of LIS at all levels with the necessary management principles and practices needed to respond proactively to diverse audiences, while also keeping a focus on the purposes of higher education. In addition, readers will find an examination of various aspects of library management and reviews on key management techniques that can be used for successful interpretation and implementation of academic library mission statements.
Includes bibliographical references (pages 81-95) and index.
Keywords: Academic libraries -- Administration